Assessment of the physicochemical conditions sediments in a polluted tidal flat colonized by microbial mats in Bahía Blanca Estuary (Argentina) - Spetter, Carla Vanesa (2015)
The aim of this work is to assess the physicochemical conditions of the supratidal sediments colonized by microbial mats at two sites from Rosales Harbor (Bahía Blanca Estuary, Argentina) close to sewage discharge. Both sites differed in the size grain. No differences in pH, Eh and temperature were observed. Moisture retention and chlorophyll a concentration were significantly different between sites and sediment layers. Heavy metals and organic matter content were significantly higher in SII. No statistical differences were found in porewater nutrients concentration, being higher in SI (except DSi). The presence of Escherichia coli in water and sediment (1000 CFU/100 mL – uncountable and 35–40 CFU g−1 dw, respectively) evidenced microbial contamination in the study area. The relationships between the physicochemical parameters evaluated and the influence of the sewage discharge allow defining two different areas in the Rosales Harbor despite the proximity and the presence of microbial mats.